In vitro Effect of the Association of Therapeutic Ultrasound to Fluconazole on the Growth Inhibition of Candida albicans - Jaine Rodrigues da Rocha; Ítalo Felipe Nogueira Ribeiro; Isaac de Oliveira Santos; Renata Sales Soares; João Rafael Valentim-Silva; Luis Eduardo Maggi; Wagner Coelho de Albuquerque Pereira; Anselmo Fortunato Ruiz Rodriguez (Archives of Current Research International, 2024)
Aims: The present work evaluated the synergistic effect of therapeutic ultrasound associated with fluconazole on Candida albicans in vitro. Place and Duration of Study: The experiments were carried out at the Phytopathology Laboratory at the Federal University of Acre (UFAC) and the Microbiology Laboratory at the Estácio Meta University Center in Rio Branco City, State of Acre, Brazil. Methodology: The experiments used a standard strain of Candida albicans (ATCC 10231). Planktonic suspensions of C. albicans were prepared and exposed to ultrasonic waves at frequencies of 1 MHz and 3 MHz, and intensity of 1.0 W/cm2, with application times of 5, 10, and 15 minutes. The treatment groups were ultrasound (UST) alone, Fluconazole alone (FLU), ultrasound combined with Fluconazole (UST + FLU), and a control group (no UST, no FLU). After 24 hours, a count of the Colony Forming Units (CFUs) was performed. Results: According to the results, a greater growth inhibition was observed in treatments (UST + FLU) at both frequencies for all three application times. It indicates that, at least in the conditions we used, therapeutic ultrasound combined with fluconazole inhibited the growth of C. albicans in vitro. The antimicrobial effect of this treatment was greater than the one with UST alone and with fluconazole alone. Conclusion: The association of antifungals with ultrasound can be considered a promising strategy to treat infections caused by fungi, allowing a reduced therapeutic period.